ANALISIS KEMAMPUAN MATEMATIKA SISWA SMK DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR TIGA VARIABEL TIPE HOT - Oktovianus Mamoh; Dominika L. Taus; Fitriani Fitriani (SIGMA, 2021)
This study aimeds to determine the mathematical ability of vocational students in solving the HOT type three-variable linear equation system problems. This research was a qualitative descriptive study. The data collection methods were written tests and interviews. The subjects of this study were nine students of class XI Pharmacy, SMK St. Agustinus Kefamenanu, Province Nusa Tenggara Timur. Two students with low mathematical ability, two students with moderate mathematical ability, and twostudents with high mathematical ability were selected to be interviewed. The research suggest that, students with high mathematical ability and students with moderate mathematical ability are able to work on questions at the analyzing and, evaluating stage, but have not yet reached the creating stage. Students are still working on problems using the method given by the teacher. Students with low mathematical ability are only able to work on problems at the analyzing stage.